2017
DOI: 10.1016/j.nbd.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

KCC3 loss-of-function contributes to Andermann syndrome by inducing activity-dependent neuromuscular junction defects

Abstract: Loss-of-function mutations in the potassium-chloride cotransporter KCC3 lead to Andermann syndrome, a severe sensorimotor neuropathy characterized by areflexia, amyotrophy and locomotor abnormalities. The molecular events responsible for axonal loss remain poorly understood. Here, we establish that global or neuron-specific KCC3 loss-of-function in mice leads to early neuromuscular junction (NMJ) abnormalities and muscular atrophy that are consistent with the pre-synaptic neurotransmission defects observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…It is noteworthy that somatic expression of MHC-I occurred in the presence of IFNγ only in electrically silent neurons (36). Interestingly, the cytotoxicity of mutant CD8 + lymphocytes is observed on electrically immature motoneurons but not on those that after 7 d in vitro become electrically mature as we showed previously (37, 38). Cytotoxic CD8 + T cells could thus contribute to the elimination of nonfunctional motoneurons during the disease.…”
Section: Discussionsupporting
confidence: 55%
“…It is noteworthy that somatic expression of MHC-I occurred in the presence of IFNγ only in electrically silent neurons (36). Interestingly, the cytotoxicity of mutant CD8 + lymphocytes is observed on electrically immature motoneurons but not on those that after 7 d in vitro become electrically mature as we showed previously (37, 38). Cytotoxic CD8 + T cells could thus contribute to the elimination of nonfunctional motoneurons during the disease.…”
Section: Discussionsupporting
confidence: 55%
“…18 The SLC12A6 cotransporter is broadly expressed throughout the brain, spinal cord and peripheral nervous system, amongst other various tissue locations. 16,19 It is inactive under isotonic conditions, but gets activated (by dephosphorylation of its C-terminus) upon cell swelling where it regulates cell volume by the efflux of K + and Clions together with water molecules across the plasma membrane. It is therefore believed to have a key role in cell volume homeostasis and neuronal activity control.…”
Section: Discussionmentioning
confidence: 99%
“…The 77% of ERRg-negative (ERRg À ) motoneurons include mainly a-motoneurons and 90% of them express TMEM16F ( Figures 2D and 2E). Co-staining with the Na + /K + -ATPase a1 subunit, a plasma membrane marker of motoneurons (Bowerman et al, 2017;Edwards et al, 2013), indicated membrane localization of TMEM16F in motoneurons ( Figure 2F). To further support expression of TMEM16F in motoneurons, we performed costaining with the pre-synaptic marker Synaptophysin.…”
Section: Tmem16f Is Expressed By A-motoneurons At Cholinergic Inputsmentioning
confidence: 99%